Changes in Healthcare Utilization up to 12 Months After COVID-19 Infection - Nora V. Becker; Rachel Parent; Theodore J. Iwashyna; John Z. Ayanian (Journal of General Internal Medicine, 2026)
Abstract Background COVID-19 infection may cause long-term changes in healthcare utilization, but heterogeneity in these changes by severity of COVID-19 infection in a national cohort is not well understood. Objective Examine a broad set of utilization measures up to 12 months after COVID-19 infection, and assess heterogeneity in utilization by whether individuals were hospitalized for their initial infection. Design Using the Merative Marketscan commercial and Medicare Advantage (MA) databases, we performed an event-study analysis comparing within-person changes in healthcare utilization after COVID-19 infection relative to before COVID-19 infection. Models were stratified by hospitalization status, and controlled for temporal changes in utilization rates, linear pre-infection trends, and observable individual confounders. Participants 901,458 adults with a diagnosis of COVID-19 infection between March 1, 2020, and December 31, 2021, enrolled continuously for 12 months before and after their infection, of whom 54,097 were hospitalized and 847,361 were not hospitalized. Main Measures Rates of admissions, emergency department (ED) visits, outpatient visits, physical therapy visits, home health services visits, and filled prescriptions for any medication. Key Results Patients hospitalized for their COVID-19 infection experienced five months of elevated re-admission risk, small declines in ED visits during post-infection months 6–12, and large relative increases in post-infection utilization of all types of ambulatory care that persisted for 12 months after infection. Patients not hospitalized for their COVID-19 infection experienced an elevated risk of admission for all post-infection months; no significant change in ED visits; small increases in outpatient visits, home health services use, and use of prescription medications; and small decreases in use of physical therapy. Conclusions We found long-lasting changes in healthcare utilization after COVID-19 infection up to a year after infection, particularly among those with more severe illness, highlighting the importance of ongoing interventions to support the needs of COVID-19 survivors.